Methamphetamine-induced psychosis: Clinical features, treatment modalities and outcomes - Eileen Thomas; Helena Lategan; Chris Verster; Martin Kidd; Lize Weich (South African Journal of Psychiatry, 2016)
Objective: To investigate the clinical features, prescribing patterns and outcomes of psychiatric inpatients admitted with methamphetamine-induced psychosis. Method: A cross-sectional, descriptive pilot study was conducted between March 2014 and August 2014 at three South African Mental Health Care Act designated hospitals prior to admission to a psychiatric hospital. Patients with methamphetamine-related psychotic symptoms according to the DSM-5 criteria were eligible. Structured face-to-face interviews were conducted and the Brief Psychiatric Rating Scale was employed as a measure of current psychopathology. Results: Fifty-six participants were included. Positive psychotic symptoms (e.g. hallucinations) were more prominent than negative symptoms (e.g. affective blunting). Almost half the participants (43%) had previous episodes of methamphetamine-induced psychosis. Within this group, all had defaulted on the prescribed treatment prior to admission. Only 29% of the participants had received prior formal substance-use rehabilitation as treatment for their disorder. High rates of comorbid cannabis and alcohol use (51%) were recorded. Most of the participants required transfer to specialist psychiatric hospitals. The amounts of methamphetamine used were not a predictor of the persistence of psychosis; however, the pattern of use was. Conclusion: Clinical features correspond with other international findings. The currently employed model of sequential, non-integrated psychiatric and substance use treatment in this setting appears ineffective.